Exploring the antidiabetic potential of Sulawesi ethnomedicines: A study of Cordia myxa and Syzygium malaccense in a Drosophila model of hyperglycemia - Nainu, Firzan; Bahar, Muhammad A.; Habibie, Habibie; Najib, Ahmad; Zubair, Muhammad S.; Arba, Muhammad; Asbah, Asbah; Mudjahid, Mukarram; Latada, Nadila P.; Filmaharani, Filmaharani; Putri, Annisa A. (Narra J, 2025)
The escalating prevalence of diabetes represents a critical challenge to global health and quality of life. Indonesia, particularly the Sulawesi region, is home to a diverse array of endemic plants with potential as sources of novel antidiabetic compounds. However, traditional preclinical models for evaluating these candidates are limited by high costs and lengthy timelines. The aim of this study was to explore the antidiabetic potential of Cordia myxa and Syzygium malaccense extracts using Drosophila melanogaster as a novel, cost-effective and efficient in vivo model. Hyperglycemia was induced in D. melanogaster larvae through a high-sugar diet, and the plant extracts were incorporated into the larval diets at concentrations ranging from 0.3125% to 2.5%. Phenotypic parameters, including body size, body weight, crawling activity, and hemolymph glucose levels, were evaluated, and the expression of metabolism-related genes (dilp2, dilp5, and srl) was analyzed using RT-qPCR. This study found that C. myxa and S. malaccense extracts improved crawling activity and body size in hyperglycemic larvae. Notably, C. myxa extract significantly reduced hemolymph glucose levels (p<0.01), increased body weight (p<0.01), and upregulated the expression of metabolic genes such as dilp2 (p<0.001), dilp5 (p<0.001), and srl (p<0.0001). In contrast, S. malaccense extract showed less pronounced effects, highlighting the efficacy of C. myxa extract in alleviating hyperglycemia and restoring metabolic homeostasis. The study highlights that C. myxa extract demonstrated promising antidiabetic properties in the Drosophila model, underscoring the utility of this model for early-stage antidiabetic drug screening and supporting further preclinical investigation into the therapeutic potential of C. myxa for managing hyperglycemia.